Insights into efficient transition metal-nitrogen/carbon oxygen reduction electrocatalysts - Wang, Hao-Yu; Weng, Chen-Chen; Yuan, Zhong-Yong (Journal of energy chemistry, 2021)
The fundamental understanding of ORR mechanism and active sites in M−N/C catalysts is introduced, and various precursors of M−N/C catalyst with the strategies for design and optimization are reviewed. [Display omitted] It is of vital importance to accelerate the sluggish oxygen reduction reaction (ORR) process at the cathode with earth-abundant metal-based catalysts for the commercialization of low-temperature polymer electrolyte membrane fuel cells. In consideration of high catalytic activity, long-term stability and low cost of potential ORR electrocatalysts, transition metal species have attracted much interest and transition metal-nitrogen-carbon (M−N/C, M = Fe, Co, Ni, Mn, etc.) catalysts have been widely considered as the most promising non-precious metal catalysts for ORR. Herein, the fundamental understanding of ORR catalytic mechanism and the identification of active centers are briefly introduced, and then different M−N/C catalysts classified by precursors with the strategies for design and optimization are highlighted. The challenges and possible opportunity for future development of high-performance ORR catalysts are finally proposed.